Early blindness results in a degraded auditory map of space in the optic tectum of the barn owl. - Knudsen, E I (1988)
The optic tectum of the barn owl (Tyto alba) contains a neural map of auditory space consisting of neurons that are sharply tuned for sound source location and organized precisely according to their spatial tuning. The importance of vision for the development of this auditory map was investigated by comparing space maps measured in normal owls with those measured in owls raised with both eyelids sutured closed. The results demonstrate that owls raised without sight, but with normal hearing, develop auditory space maps with degraded precision and with aspects of topography that are abnormal.